Crosstalk between gut microbiota and renal ischemia/reperfusion injury - Huang, Peng; Cao, Jianwei; Chen, Jingyi; Luo, Yanrong; Gong, Xiaofang; Wu, Chengyi; Wang, Yu (Frontiers in Cellular and Infection Microbiology, 2022)
Renal ischemia-reperfusion injury (IRI) is the main cause of acute kidney injury and the cause of rapid renal dysfunction and high mortality. In recent years, with the gradual deepening of the understanding of the intestinal flora, exploring renal IRI from the perspective of the intestinal flora has become a research hotspot. It is well known that the intestinal flora plays an important role in maintaining human health, and dysbiosis is the change in the composition and function of the intestinal tract, which in turn causes intestinal barrier dysfunction. Studies have shown that there are significant differences in the composition of intestinal flora before and after renal IRI, and this difference is closely related to the occurrence and development of renal IRI and affects prognosis. In addition, toxins produced by dysregulated gut microbes enter the bloodstream, which in turn exacerbates kidney damage. This article reviews the research progress of intestinal flora and renal IRI, in order to provide new treatment ideas and strategies for renal IRI.